Molecular serogrouping of Escherichia coli. (22nd February 2018) - DebRoy, Chitrita; Fratamico, Pina M.; Roberts, Elisabeth
Abstract: O-antigens present on the surface of Escherichia coli provide antigenic specificity for the strain and are the main components for O-serogroup designation. Serotyping using O-group-specific antisera for the identification of E. coli O-serogroups has been traditionally the gold-standard for distinguishing E. coli strains. Knowledge of the O-group is important for determining pathogenic lineage, classifying E. coli for epidemiological studies, for determining virulence, and for tracing outbreaks of diseases and sources of infection. However, serotyping has limitations, as the antisera generated against each specific O-group may cross-react, many strains are non-typeable, and others can autoagglutinate or be rough (lacking an O-antigen). Currently, the nucleotide sequences are available for most of the 187 designated E. coli O-groups. Public health and other laboratories are considering whole genome sequencing to develop genotypic methods to determine O-groups. These procedures require instrumentation and analysis that may not be accessible and may be cost-prohibitive at this time. In this review, we have identified unique gene sequences within the O-antigen gene clusters and have targeted these genes for identification of O-groups using the polymerase chain reaction. This information can be used to distinguish O-groups by developing other platforms for E. coli diagnostics in the future.